Effect of Plastics (Geotextiles) on Heavy Metal Accumulation by Industrial Hemp Plants Cultivated in Polluted Mediterranean Soils - Dimitrios Alexiadis; John Bethanis; Sotiria G. Papadimou; Edoardo Barbieri; Rafaella Vogia; Eftihia Tatsi; Pavlos Tziourrou; Eleni Tsaliki; Evangelia E. Golia (International Journal of Plant Biology, 2025)
An attempt was made to simulate the conditions prevailing in an agricultural crop to investigate whether and how geotextile microplastics alter the movement and accumulation of heavy metals in plants. For this purpose, a pot experiment, lasting 149 days, was carried out on soil obtained from a rural area, where pieces of a geotextile in mesoplastic dimensions, of the same chemical composition as that used by farmers in the Greek countryside, were added. Furthermore, metal solutions (Cu, Zn, Cd) were incorporated in the pots at two levels, and incubation prior to planting was carried out for two weeks. Then, industrial hemp was cultivated, while continuous measurements of its horticultural characteristics and of the levels of metals moved from the soil to the plant were made. The plants appeared to be highly resistant to the rather harsh growing conditions, and furthermore, it was observed that the cumulative metal capacity of cannabis was enhanced in most cases. The simultaneous presence of metals and geotextile (plastic) fragments enhanced the amount of Zn and Cd transfer into the soil-to-plant system. Hemp plants exhibited strong resilience abilities in the particularly stressful soil environment, possibly developing defense mechanisms. The experiments are particularly encouraging as they prove that simple and habitual practices in cultivated soils that lead to post-weather erosion of the geotextile may contribute positively in terms of remediation methods for heavy-metal-laden soils, as they indirectly help the plant to remove larger amounts of metal elements. The experiments should be intensified on a wider range of soils of different soil reactions and particle sizes and, of course, should be carried out under real field conditions in Mediterranean soil environments.